Beating versus arrested heart isolated tricuspid valve surgery: An 11‐year experience in the current era. Issue 3 (1st February 2021) - Flagiello, Michele; Grinberg, Daniel; Connock, Martin; Armoiry, Xavier; Buzzi, Remi; Thibault, Helene; Uhlrich, William; Jacquet‐Lagreze, Matthias; Fellahi, Jean L.; Obadia, Jean F.; Pozzi, Matteo
Abstract: Background and aim of the study: Data about the beating heart (BH) technique for isolated tricuspid valve (TV) surgery compared to the arrested heart (AH) technique are sparse. We compared the outcomes of isolated TV surgery between BH and AH technique. Methods: We performed an observational analysis of our database of isolated TV surgery. Patients were divided into two groups according to whether surgery was performed without (BH group) or with (AH group) aortic cross‐clamping and cardioplegic arrest. The primary endpoint was survival to hospital discharge. Risk factors for in‐hospital mortality were searched with multivariate analyses. We undertook further comparisons after propensity‐score matching. Results: From January 2007 to December 2017, we performed 82 isolated TV surgery (BH group, n  = 47, 57.3%; AH group, n  = 35, 42.7%). The mean age was 59.1 years, 56.1% were female. BH group patients were older (61.8 vs. 55.4 years; p  = .035), had greater impaired renal function (glomerular filtration rate, 61.1 vs. 74.6 ml/min; p  = .012), were more frequently operated for secondary TR (61.7 vs. 31.4%; p  = .008), underwent more frequently a reoperation (53.2 vs. 28.6%; p  = .042) and exhibited a higher surgical risk (EuroSCORE II, 3.92 vs. 2.50%; p  = .013). In‐hospital mortality was not different between both groups, either considering unmatched (BH = 10.6 vs. AH = 5.7%; OR = 1.96, 95% confidence interval [CI] = 0.36–10.77) or matched populations (BH = 10.6 vs. AH = 6.4%; OR = 1.89, 95% CI = 0.36–9.97). Age was the only predictor of in‐hospital mortality. Conclusions: The BH technique showed comparable outcomes to the AH technique for isolated TV surgery despite a higher risk profile.